??????? ???????? ?? ??????? ?????? ?? ??????? ????? ??????? (??????? ?????????????????? ???????? ??? ??????? ??????): Multiple Intelligence Assessment and Application in Arabic Language Education (Musical Intelligence, Interpersonal Intelligence, and Natural Personality) - Puti Rindang Sari; Dewi Chamidah (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
?????? ?????: ????? ???????? ???????? ??????? ?????? ?? ??????? ???? ?????? ????? ???? ??? ?????? ????????? ??????? ??????? ??????? ??????? ??????? ???????. ?????? ??? ??????? ????? ????? ???????? ?????????? ????? ?????. ???????? ???? ?? ?????? ????? ?? ???????? ?????? ????? ???????? ????????? ???????? ????????. ????? ????? ????? ???????? ???????? ??????? ?????????? ?????? ?????? ??? ?? ???? ??????? ??? ???????? ???????? ???? ?????? ????? ???? ?? ????? ???? ????? ???? ?? ????? ????????? ????????. ?? ??? ???????? ???????? ???? ??????? ?? ?? ????? ????? ????? ???????. ???????? ???????? ????? ??? ??????? ?????? ?? ????? ?? ????? ??????? ??????? ??? ???? ????? ??? ????? ???????? ??? ????? ???????? ????????? ???????? ??????. ??????? ????????: ??????? ??????? ????????? ???????? ????? ???????. Abstract: Multiple intelligences have different types of intelligence, four of which will be discussed: musical intelligence, intrapersonal intelligence, intrapersonal intelligence, and naturalistic intelligence. This study uses a qualitative method using a literature study strategy. Data obtained from observation, reading books related to multiple intelligences, and documentation. The results of the study of multiple intelligences are a very extraordinary concept today, as children are not only interested in high grades, but they can also see that the child has their own advantages according to their multiple intelligences. In these multiple intelligences there is an application in every skill for learning the Arabic language. Multiple intelligences themselves have their own way of assessing or evaluating the correct way for each intelligence associated with each skill as well as training students' perseverance, skills and cooperation. Keywords: Word, Multiple intelligences, evaluation, Arabic Language